Systematic Literature Review: The Effect of Experiential Learning (EL) on Learning Outcomes - Dewi Syafriani; Retno Dwi Suyanti; Ani Sutiani (Jurnal Penelitian Pendidikan IPA, 2025)
Experiential Learning (EL) is one of the 21st century learning models that provides students with more real and applicable learning experiences. Although EL has been widely used in various learning, there is still no comprehensive synthesis of how EL can be effectively implemented in various learning contexts to achieve various learning outcomes. This research aims to identify and synthesise the effectiveness of EL in improving and developing various learning outcomes. This research uses the Systematic Literature Review (SLR) method by analysing search results from the Scopus, Erics, Web of Science, and Google Scholar databases, in the last 10 years (2025-2015). Based on the search results, 16 suitable articles were obtained based on the inclusion and exclusion criteria. The results of the analysis of this article review can be drawn conclusions and findings that EL has a good impact on improving various learning outcomes, such as improving academic achievement, critical thinking skills, higher order thinking skills, collaboration, learning motivation, self-learning readiness, activeness, pedagogical skills, and problem-solving skills both at the elementary, junior high school, high school/vocational school and university levels. This research provides a comprehensive synthesis of the effectiveness of EL in improving and developing various learning outcomes.